Evaluating the performance of transport equations through long-term records of integrative measured bedload data - Andrea Lammer; Rolf Rindler; Michael Tritthart; Marcel Liedermann; Markus Moser; Dorian Shire-Peterlechner; Sabrina Schwarz; Helmut Habersack (International Journal of Sediment Research)
Temporal and spatial variability and a wide range of measured transport rates at comparable flow rates are well-known characteristics of the bedload transport process but represent substantial difficulties in practice and for load calculation. The possibility of measuring the bedload transport process has increased in recent years through the use of technically advanced methods. Since 2011, an integrative bedload monitoring system has been operating on the Urslau River in Austria and has been continuously observing the transport process. This long-term integrative dataset provides the basis for comparing calculation results from commonly used bedload transport formulae with measured data. On the basis of 27 high sediment transport efficiency events, as well as 75 events with reduced sediment availability and 34 events with low sediment availability, this study compares the measured and calculated bedload volumes. In addition, a wide range of measured bedload transport rates are presented for comparable discharges, and values in this range are represented by the formulae shown. The performance of the transport equations is improved by considering measured data from integrative bedload monitoring and by classifying bedload events. The results presented here indicate that, depending on the question considered and by selecting the appropriate formula, it is possible to achieve improved calculation results for practice that are comparable to the measured values.